Continental influx and pervasive matrilocality in Iron Age Britain - Lara M. Cassidy; Miles Russell; Martin Smith; Gabrielle Delbarre; Paul Cheetham; Harry Manley; Valeria Mattiangeli; Emily M. Breslin; Iseult Jackson; Maeve McCann; Harry Little; Ciarán G. O’Connor; et al. (Nature, 2025)
Abstract Roman writers found the relative empowerment of Celtic women remarkable1. In southern Britain, the Late Iron Age Durotriges tribe often buried women with substantial grave goods2. Here we analyse 57 ancient genomes from Durotrigian burial sites and find an extended kin group centred around a single maternal lineage, with unrelated (presumably inward migrating) burials being predominantly male. Such a matrilocal pattern is undescribed in European prehistory, but when we compare mitochondrial haplotype variation among European archaeological sites spanning six millennia, British Iron Age cemeteries stand out as having marked reductions in diversity driven by the presence of dominant matrilines. Patterns of haplotype sharing reveal that British Iron Age populations form fine-grained geographical clusters with southern links extending across the channel to the continent. Indeed, whereas most of Britain shows majority genomic continuity from the Early Bronze Age to the Iron Age, this is markedly reduced in a southern coastal core region with persistent cross-channel cultural exchange3. This southern core has evidence of population influx in the Middle Bronze Age but also during the Iron Age. This is asynchronous with the rest of the island and points towards a staged, geographically granular absorption of continental influence, possibly including the acquisition of Celtic languages.